Cognitive Behavior Therapy (CBT) pada anak yang mengalami Attention Deficit Hyperactivity Disorder (ADHD): Sebuah tinjauan literatur - Iceu Amira; Hendrawati Hendrawati; Indra Maulana; Sukma Senjaya (Holistik Jurnal Kesehatan, 2022)
Background: Attention Deficit-Hyperactivity Disorder (ADHD) is a psychiatric condition that has long been known to affect children's ability to function. Children with ADHD show incompetence not only in attention and focus therapy but also in decision-making and emotional regulation. It is therefore important to diagnose and treat the disorder at a young age so that the symptoms do not continue into adulthood.Purpose: To determine the benefits of cognitive behavioral therapy in children with attention deficit hyperactivity disorder (ADHD). Method uses study literature review with a PICO search strategy on three databases, namely Pubmed, Sage Journals, and EBSCO CINAHL. Results: Obtained articles from European countries, Israel, Franch and Korea according to the research inclusion criteria. From the results of the analysis, it was found that the CBT interventions that can be given to children with ADHD are Cognitive Executive Function (EF) and Cognitive-Functional Intervention.Conclusion: The results of the study found that CBT can improve executive function which leads to increased independent learning performance in children with ADHD.Keyword: Cognitive Behavior Therapy (CBT); Children; Hyperactivity Disorder (ADHD)Pendahuluan: Attention Deficit-Hyperactivity Disorder (ADHD) adalah kondisi kejiwaan yang telah lama diketahui mempengaruhi kemampuan fungsi anak. Anak dengan ADHD menunjukkan ketidak mampuan tidak hanya dalam perhatian dan fokus tetapi juga dalam pengambilan keputusan dan pengaturan emosi. Maka dari itu penting untuk mendiagnosis dan mengobati gangguan pada usia muda sehingga gejalanya tidak berlanjut hingga dewasa.Tujuan: Untuk mengetahui manfaat cognitive behavioral therapy pada anak dengan attention deficit hyperactivity disorder (ADHD).Metode: Menggunakan studi literatur review dengan strategi pencarian PICO pada tiga database yaitu Pubmed, Sage Journals, dan EBSCO CINAHL. Hasil : Didapatkan artikel yang berasal dari negara Eropa, Israel, Prancis dan Korea sesuai dengan kriteria inklusi penelitian. Dari hasil analisis didapatkan bahwa intervensi CBT yang dapat diberikan pada anak dengan ADHD adalah Cognitive Executive Function (EF) dan Cognitive-Functional Intervention.Simpulan: Ditemukan bahwa CBT dapat meningkatkan fungsi           eksekutif yang mengarah pada peningkatan kinerja belajar mandiri pada anak dengan ADHD.